Synthesis and Characterization of Rare Earth Ion Doped Nano ZnO - John, Rita; Rajakumari, Rajaram (Nano-Micro Letters, 2012)
Zinc oxide (ZnO) doped with erbium at different concentrations was synthesized by solid-state reaction method and characterized by X-ray diffraction (XRD), scanning electron microscopic (SEM), UV-absorption spectroscopy, photoluminescence (PL) study and vibrating sample magnetometer. The XRD studies exhibit the presence of wurtzite crystal structure similar to the parent compound ZnO in 1% Er3+ doped ZnO, suggesting that doped Er3+ ions sit at the regular Zn2+ sites. However, same studies spread over the samples with Er3+ content>1% reveals the occurrence of secondary phase. SEM images of 1% Er3+ doped ZnO show the polycrystalline nature of the synthesized sample. UV-visible absorption spectrum of Er3+ doped ZnO nanocrystals shows a strong absorption peak at 388 nm due to ZnO band to band transition. The PL study exhibits emission in the visible region, due to excitonic as well as defect related transitions. The magnetization-field curve of Er3+ doped ZnO nanocrystals showed ferromagnetic property at room-temperature.